2011
DOI: 10.1182/blood-2010-02-269753
|View full text |Cite
|
Sign up to set email alerts
|

Radioimmunotherapy of relapsed indolent non-Hodgkin lymphoma with 131I-rituximab in routine clinical practice: 10-year single-institution experience of 142 consecutive patients

Abstract: Radioimmunotherapy of indolent non-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 31 publications
1
41
0
Order By: Relevance
“…A previous study by Michael et al found that the toxicity of 131 I-rituximab in a total of 142 patients with lymphoma was mainly self-limited myelosuppression, with grade 4 thrombocytopenia and grade 4 neutropenia in 6 % and 10 % of cases, respectively [14]. The only toxicity observed in our patient was a grade 1 thrombocytopenia, without anemia and neutropenia.…”
supporting
confidence: 50%
“…A previous study by Michael et al found that the toxicity of 131 I-rituximab in a total of 142 patients with lymphoma was mainly self-limited myelosuppression, with grade 4 thrombocytopenia and grade 4 neutropenia in 6 % and 10 % of cases, respectively [14]. The only toxicity observed in our patient was a grade 1 thrombocytopenia, without anemia and neutropenia.…”
supporting
confidence: 50%
“…Over one third (13/31) of our patients have achieved more than 5 years relapse-free survival. The choice of 131I-rituximab RIT as the main therapy was taken after meticulous in-house development, calculation of individual dosimetry, and extensive published evidence of efficacy [8,9,10,14].…”
Section: Discussionmentioning
confidence: 99%
“…We have administered iodine-131 rituximab radioimmunotherapy ( 131 I-rituximab RIT) to treat patients with relapsed or refractory indolent non-Hodgkin lymphoma, most of whom had follicular lymphoma, with an objective overall response rate of 76% with a 4 year actuarial survival rate of 59% ± 10% with minimal toxicity [8]. We reported our clinical experience of the same treatment in 142 consecutive patients with relapsed low grade non-Hodgkin lymphoma, predominantly FL, where objective response rate (ORR) of 67%, complete remission rate (CR) of 50%, and 8 year overall survival (OS) of 48% were observed [9]. We have also treated a cohort of 68 FL patients first-line with 131I-rituximab radioimmunotherapy achieving 98% ORR and 89% CR in a prospective Phase II clinical trial [10].…”
Section: Introductionmentioning
confidence: 98%
“…Recently, it was reported that frontline use of cladribine and rituximab can induce an overall response rate of 87%, with 61% of patients achieving complete remission, suggesting use of this combination for the initial treatment of MCL 83 . Radioimmunotherapy with 90 Y-labeled anti-CD20 monoclonal antibody (ibritumomab tiuxetan) or 131 I-rituximab is now being tested in phase I-II trials, including stem cell transplant setting [84][85][86][87] .…”
Section: New Agentsmentioning
confidence: 99%